Evaluation of the genetic diversity of Bauhinia winitii an endemic plant of Thailand, using microsatellite markers - Supajit Sraphet; Poonyapat Sukawutthiya; Nattaya Srisawad; Smith, Dunkan R.; Kanokporn Triwitayakorn (2021)
"Bauhinia winitii Craib is an endemic species native to Thailand. Genetic diversity was assessed using microsatellite markers developed from a library enriched using (AG)20/(CAG)20 oligonucleotide probes. Eight polymorphic loci produced a total of 28 alleles with a mean number of 3.5 alleles per locus from 33 specimen of B. winitii. The averages of the expected (He) and observed (Ho) heterozygosity were 0.418 and 0.394, respectively. The average value of polymorphic information content (PIC) was 0.364 and two SSR loci were highly informative"-title page.
Includes bibliographical references (pages 549-552).
Keywords: Bauhinia -- Thailand; Endemic plants -- Thailand